PEMANFAATAN SISTEM INFORMASI REKAM MEDIS BERBASIS WEB PADA PUSKESMAS KANDA - Rasna, Rasna; Nurhayati, Siti; Sah, Andrian; Tonggiroh, Mursalim; Widiyantoro, Riandi; Matdoan, Irjii (Gapenas Publisher, 2025)
Health services at Puskesmas Kanda still face challenges in managing medical record data, which is mostly done manually. Manual data recording and reporting often cause data duplication, lost archives, and delays in generating health reports. To overcome these issues, this Community Service (PkM) activity was carried out by the Faculty of Computer Science, Universitas Yapis Papua, through training and mentoring on the implementation of a web-based medical record information system. The main objective was to improve the skills of health workers in operating the system to accelerate data recording, reduce human error, and enhance service efficiency. The activity was conducted through several stages: survey and observation, preparation of training materials, hands-on practice (learning by doing), and post-training evaluation. The results showed a significant improvement in participants’ ability to manage medical record data digitally. About 90% of participants stated that the system was easy to use and improved service speed, while 88% found the training relevant to their daily work. This activity had a positive impact on improving digital literacy among health workers and supported the digital transformation of primary health services in Papua.